Efficient H2 production via membrane-assisted ethanol steam reforming over Ir/CeO2 catalyst. (20th September 2019) - Jia, Haiyuan; Zhang, Jixin; Yu, Jiafeng; Yang, Xiaodeng; Sheng, Xueru; Xu, Hengyong; Sun, Chenglin; Shen, Wenjie; Goldbach, Andreas
Abstract: Ethanol steam reforming in membrane reactors is a promising route for decentralized H2 production from biomass because H2 yield can be greatly enhanced due to the equilibrium shift triggered by instantaneous H2 extraction. Here a highly active Ir/CeO2 catalyst has been combined with ca. 4 μm thin Pd membranes employing a 6:1 steam/ethanol feed between 673 K and 873 K at reforming pressures up to 1.8 MPa. The H2 yield reached 94.5% at 873 K and 1300 kPa due to the separation of 91.8% H2 whereas H2 yield was limited to 28.9% without membrane. At lower temperatures and pressures sweep gas was needed at the membranes' permeate side for efficient H2 generation since the H2 partial pressure remains equilibrium-limited on the reaction side. Furthermore, the H2 yield improved from 63.0% to 84.7% at 773 K, 1500 kPa and sweep-to-feed flow ratio 0.5 when the distance between membrane and reactor wall was shortened by ca. 30%. Thus, external H2 diffusion towards the membrane has a large impact on membrane reactor performance pointing towards microstructured membrane reactors as optimum devices for sustainable H2 production from biomass. Highlights: Highly active Ir/CeO2 catalyst combined with highly permeable Pd membranes. Thermodynamic constraints necessitate utilization of sweep gas up to 773 K. H2 yield and H2 recovery factor depend strongly on mass transfer in catalyst bed. 94.5% H2 yield with 91.8% H2 recovered at 873 K without sweep gas.